Catalogue of fungi in China 4: Didymiaceae and Physaraceae (Myxomycetes) - Xuefei Li; Jiajun Hu; Yonglan Tuo; You Li; Dan Dai; Frederick Leo Sossah; Minghao Liu; Jiajia Wang; Jiage Song; Bo Zhang; Xiao Li; Yu Li (Mycology)
Myxomycetes play crucial ecological roles, yet their species diversity, distribution, and taxonomic relationships remain poorly understood. In this study, we examined 104 specimens from 19 provinces in China. Through morphological analysis, we identified a group of species with reduced lime formation, a feature typically associated with the Physaraceae, but with key morphological similarities to the Diderma. A comprehensive phylogenetic analysis was conducted using three genes (nSSU, EF-1α, and COI), resulting in a dataset of 452 sequences from 116 species. Notably, we identified a distinct clade within Didymiaceae containing species with fewer lime knots, a trait traditionally linked to Physaraceae. This clade, designated as the new genus Neodiderma, was phylogenetically positioned as a sister group to Diderma, potentially representing a transitional group between Didymiaceae and Physaraceae, supported by both morphological and molecular evidence. Eleven new species — N. macrosporum, N. pseudobisporum, N. verrucocapillitium, N. rigidocapillitium, N. rufum, Physarum guangxiense, P. subviride, P. nigritum, P. biyangense, P. neoovoideum, and P. jilinense — were identified from China, and their phylogenetic positions were analysed. Additionally, N. spumarioides (formerly Diderma spumarioides) was recombined. The new and recombined species were formally described and illustrated, and a key to the sections and species of Neodiderma and Physarum was provided.